Research on Business English Teaching in Chinese Universities - Zheng, Jinjie (Transactions on Social Science, Education and Humanities Research, 2024)
With the deepening of the development trend of economic globalization and cultural globalization, business English teaching has ushered in a good opportunity for development. However, the market demand for business English professionals' comprehensive ability and quality is also increasing. Based on the literature and the actual situation, this thesis summarizes the current situation of business English teaching in Chinese universities and gives some suggestions for solving the current problems. Therefore, universities should optimize the current business English teaching mode according to the market demand and job requirements, based on the actual development of the business English teaching profession, and optimize the current business English teaching mode in a targeted manner to improve the current predicament. After mastering the qualities and advantages of task teaching methods, inter-disciplinary simulation training, and online teaching platforms, we can effectively infiltrate them into all aspects of business English teaching and comprehensively strengthen the construction of a task-driven business English teaching system. In this way, not only can we cultivate more high-quality applied and compound business English talents needed by society, but we also make business English teaching break through the current educational development difficulties.